Quantitative analysis of gingival phenotype in different types of malocclusion in the anterior esthetic zone - Surekha Ramrao Rathod; Noopur Pradeep Gonde; Abhay Pandurang Kolte; Pranjali Vijaykumar Bawankar (Wolters Kluwer Medknow Publications, 2020)
Background: For any esthetic treatment planning, the shape and form of gingiva should be a prime factor of concern. The correct identification of gingival phenotype (GP) ensures a firm foundation for future health and prognosis of the treatment indicated. Hence, the aim of the present study was to evaluate the correlation between the GP in the anterior esthetic zone with different types of maloclussion and severity of crowding. Materials and Methods: A total of 110 periodontally healthy controls were equally divided into two groups depending on the type of malocclusion. They were further divided according to the levels of dental crowding as mild, moderate, and severe. GP was measured on the anterior esthetic teeth using transgingival probing, and width of the attached gingiva (WAG) was measured using histochemical staining method. Results: In severe crowding group, the GP in 12 and 22 region was found to be thick (P = 0.035) while, in 32 and 42 region was thin (P = 0.042). The WAG shows a significant difference between WAG with 23 in severe crowding group with P = 0.042, whereas there was no significant relationship found between the GP with Angle's classification. Conclusion: Within the limitations of the study, it can be concluded that the teeth in the maxillary and mandibular anterior esthetic region showed the thin phenotype. When the severity of crowding increases, the GP and WAG vary depending on the position of the tooth. There is no association between the Angle's classification and the mean GP of the maxillary and mandibular anterior region teeth.